Microbial quality of mung beans (Vigna radiata Linn.) sprouts in Malabon, Valenzuela, Philippines - Berja, Mirasol Cis (2005)
ABSTRACT This study was undertaken to assess the microbial quality of retail mung bean sprouts sold in wet markets of Malabon and Valenzuela, Philippines. The production, transportation, and vending procedure of mung bean sprouts in wet markets were documented. The TPC of the mung bean sprouts obtained ranged from 7.59 to 10.61 log10 cfu/g. Yeast and mold counts of the selected five wet markets ranged from 4.00 to 6.15 log10 cfu/g. For the lactic acid bacteria counts, the highset and lowest counts were 7.55 and 10.29 log10 cfu/g, respectively. The values ranged from 5.23 to 6.61 log10 cfu/g for coliform counts and 2.15 to 4.50 log10 cfu/g for Generic Escherichia coli Count. Salmonella spp. were detected in all test market samples. The differences of counts from various wet markets may be explained by the sanitary conditions prevailing in the markets as well as occurrence of contamination during production and distribution. For the thermal inactivation of Salmonella typhimurium E1366 in mung bean sprouts, the D-values obtained were 0.29, 0.28, 0.12 min at 60, 70, and 90°C, respectively. It was established in this study that heat treatment could effectively reduce inoculated S. typhimurium in mung bean sprouts.